Estimating flows and metal recovery values of waste printed circuit boards in Australian e-waste. (15th June 2019) - Golev, Artem; Corder, Glen D.; Rhamdhani, M. Akbar
Highlights: Waste printed circuit boards (PCBs) represent a valuable material for recycling. Limited statistics maintains an uncertainty in estimating feedstock of waste PCBs. Australia generates about 25 kt of waste PCBs a year with 40% recovery rate (2014). Major metals in recovered PCBs are gold (1.28 t), PGMs (0.5 t) and copper (1.3 kt). Better reporting is crucial for establishing domestic metal recovery from PCBs. Abstract: This paper overviews current situation with e-waste management in Australia, focusing on material flows and metal recovery values of waste printed circuit boards (PCBs). PCBs often contain high concentrations of precious and other metals representing the most valuable material for recycling from e-waste. The amount of recovered PCBs from e-waste in Australia is estimated at up to 10 kt per year or 40% (2014), with potential metal recovery value of US$ 78 m or AUD 100 m (2014). However, most of collected PCBs are exported for recycling overseas, resulting in lost economic opportunities. The findings from this study represent the first comprehensive country-wide estimation of volumes, destiny and metal recovery values for waste PCBs. While many figures are indicative and expert opinion based, they help overcome the limitations of the official statistics for e-waste in Australia and provide important data for a feasibility study if the metal recovery operations for PCBs are to be considered in the country.